IMPLIKASI PERAN GANDA ISTRI SEBAGAI PENCARI NAFKAH TERHADAP HAK DAN KEWAJIBAN SUAMI ISTRI - Amany, Jihan; Muhtadin, Sabilul (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2026)
This study is motivated by the escalating involvement of wives as breadwinners, driven by familial economic pressures that render husbands unable to fully meet household needs. Existing literature examines the implications of wives’ dual roles as earners on spousal rights and obligations, while fewer studies explore factors propelling wives into employment and shifts in domestic task division. The research was conducted in the Sokka brick factory area, Kebumen Regency, which predominantly employs women as wives and housewives. The primary objectives are to analyze the backgrounds of wives’ workforce participation, the implementation of spousal rights and duties, and the impacts of dual roles on household dynamics. A qualitative approach employing a case study design was utilized, with data gathered through participatory observation, in-depth interviews, document analysis, and literature review involving seven key informants. Findings reveal that economic factors and social contexts serve as primary drivers of wives’ employment. The dual roles enhance family economic welfare, strengthen spousal partnerships, and promote collaborative decision-making, albeit inducing significant physical fatigue and emotional strain.